PENGARUH MOTIVASI BELAJAR, INTEGRITAS MAHASISWA, DAN PENYALAHGUNAAN TEKNOLOGI INFORMASI TERHADAP PERILAKU KECURANGAN AKADEMIK - Nabilah Sarah Hafizhah; Fajar Syaiful Akbar (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This research has been established to examine the influence of learning motivation, student integrity and the misusage of information technology towards academic fraud. The sampling method that has been applied for conducting this research is called probability sampling using the random sampling method as a probability sampling technique. In carrying out this research, samples have been taken among 171 students who graduated in accountancy with a bachelor's degree from UPN "Veteran" East Java in the years 2017 and 2018. The result of this research indicates that learning motivation does not have a positive impact on academic fraud. Nevertheless, with regards to student integrity and the misusage of information technology, the result shows that these do have a positive yet significant influence on academic fraud.